THE IMPACT OF PATH-GOAL LEADERSHIP BEHAVIOUR ON GROUP COHESIVENESS: A JAPANESE ELECTRONIC COMPANY AND SINGAPOREAN ELECTRONIC COMPANY IN JOHOR - Aris, Amir; Kamarudin, Mohd Fauzi (Journal of Human Capital Development (JHCD), 2009)
This study seeks to determine the impact of Path-Goal leadership on group cohesiveness between line managers in two electronics companies, one a Japanese and the other a Singaporean in Johor Bahru, Johor. The objectives of the study are 1) to seek characteristics of Path-Goal leadership behaviour often displayed by a manager of an organization. 2) to seek the effects of Path-Goal leadership behaviour towards group cohesiveness? One hundred and one Line Managers were selected as respondents of the study. Questionnaire was the main instrument used in this study. The first questionnaire was developed by Yulk (1981) and further improved by Aminuddin (1992). This was used to measure Path-Goal leadership. The second questionnaire is by Dobbins and Zaccaro (1986) which was used to measure group cohesiveness. The data was analyzed through descriptive and inferential statistical methods. The result showed that supportive leadership behaviours were present at the Japanese company whilst directive top down leadership behaviours at the Singaporean company. The result was significant for the Singaporean company where the Path-Goal leadership style practiced affected group cohesiveness at r2 = 0.305, P< 0.05. However, the Path-Goal leadership in the Japanese Company did not have an impact on group cohesiveness recorded at r2 = 0.167, P< 0.05. Keywords: leadership, path-goal theory, strategic management, research, evaluation